The Role of Schools as a Social System in Efforts to Implement Multicultural Values ​​at SMKN 2 Mataram - Almira Wulandari; Cinta Nurhidayah; Auliya Rahmawati; Anindya Rospianita; Yunita Utami Putri; Sawaludin (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to analyze the role of the school as a social system in implementing multicultural values at SMKN 2 Mataram. By using descriptive qualitative methods, which are based on the characteristics of a phenomenon or problem. Data was collected through observation, interviews and documentation methods carried out at the research location. The research results show that 1) SMKN 2 Mataram plays a significant role as a social system by providing activities and programs based on multicultural values, 2) SMKN 2 Mataram's efforts are to implement programs such as Civics Learning, Cultural Saturdays, Project for Strengthening Pancasila Student Profiles (P5 ) and other efforts such as anti-bullying seminars and counseling by guidance and counseling teachers that strengthen students' understanding of diversity. 3) Supporting factors for implementing multicultural values include adequate facilities and infrastructure, full support from teachers, and the use of modern learning media. Then there are obstacles such as uneven student participation and a lack of awareness among some students of the importance of multicultural values.